APPLICATION OF GROUP INVESTIGATION (GI) COOPERATIVE LEARNING MODEL TOWARDS STUDENTS` PROBLEM SOLVING SKILLS ON ENVIRONMENTAL POLLUTION CONCEPTS - nesia premurdia; Tri Jalmo; rini rita marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
This study aims to find out  the improvement of students` problem solving skills on environmental pollution and conservation concepts of  X grade student of  SMA N 1 Talang Padang using Group Investigation learning model. The  study  used  pretest-posttest non equivalent design. Sample were X5 as experimental class and X3 as control  chosen from population using  randomized block  sampling technique. Data of students problem solving skill was obtained using  pretest and posttest, while data of  students` learning activities was observed and the data obtained was statistically analyzed using t-test with SPSS 17 program.The study  showed  that there was  improvement of students` problem solving skills  with  61.67 N-gain score. The GI learning model effected  students` problem solving significantly espescially on three aspects such as  identifying problem, formulating problem, and giving alternative solution.The GI learning model also  affected students` learning activities significantly on the students  expressing opinions / ideas  skill and discussions. The study concluded that the GI  learning models can improve students' problem solving skills and enhance student learning activities on environmental pollution and conservation concepts.Key words:     Group Investigation (GI) learning model, problem solving skills, learning activities, environmental pollution, environmental conservation.